2022
DOI: 10.1002/ejic.202100927
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Ferrocenyl−Iodotriazoles and −Iodotriazoliums as Halogen Bond Donors. Synthesis, Solid State Analysis and Catalytic Properties.

Abstract: Despite the increasing number of applications based on halogen bond (XB), asymmetric catalysis purely based on such supramolecular interactions still remains a huge challenge. The first step toward its development is the design of appropriate XB chiral donor molecules with good catalytic properties. In this context, we report the synthesis of a series of iodinated compounds based on the triazole or triazolium ring and possessing the planar chirality of ferrocene. Their XB donor property was attested by X‐ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 73 publications
0
18
0
1
Order By: Relevance
“…Low asymmetric induction (6.4%) was observed in the reaction with an enantiopure bidendate catalyst. 824 Exploring the asymmetric pnictogen-bonding catalysis, Tan and coauthors reported an enantioselective transfer hydrogenation of benzoxazines catalyzed by a novel chiral antimony cation/ anion pair. 825 The catalyst showed remarkable efficiency and enantiocontrol even at 0.05 mol % loading.…”
Section: Chemicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Low asymmetric induction (6.4%) was observed in the reaction with an enantiopure bidendate catalyst. 824 Exploring the asymmetric pnictogen-bonding catalysis, Tan and coauthors reported an enantioselective transfer hydrogenation of benzoxazines catalyzed by a novel chiral antimony cation/ anion pair. 825 The catalyst showed remarkable efficiency and enantiocontrol even at 0.05 mol % loading.…”
Section: Chemicalmentioning
confidence: 99%
“…Good catalytic activity was observed at room temperature with an iodotriazolium triflates in an aza-Diels–Alder reaction, and the best performance was achieved with a bidendate derivative. Low asymmetric induction (6.4%) was observed in the reaction with an enantiopure bidendate catalyst . Exploring the asymmetric pnictogen-bonding catalysis, Tan and co-authors reported an enantioselective transfer hydrogenation of benzoxazines catalyzed by a novel chiral antimony cation/anion pair .…”
Section: Trends In Enantioselective Recognition In Natural and Synthe...mentioning
confidence: 99%
“…More recently, our groups described the bis-iodotriazolium catalyst 38 bearing planar chirality of ferrocene. This bidendate catalyst performed efficiently in the aza-Diels–Alder reaction between imine 39 and Danishefsky diene 40 , but product 41 was obtained with a very low ee of 6%, probably because of the high flexibility of the two iodotriazolium arms of the catalyst [ 99 ] ( Figure 20 ).…”
Section: Asymmetric Catalysismentioning
confidence: 99%
“…Since, halogenated ferrocenes have appeared as key intermediates for accessing polysubstituted ferrocenes [12]. More recently, iodinated ferrocenes turned out to be involved in halogen bond (XB) in solid state [13,14], and even in solution with emerging application as organocatalyst in organic synthesis [13,15].…”
Section: Introductionmentioning
confidence: 99%